HUBUNGAN TINGKAT PENGETAHUAN IBU TERHADAP PERILAKU HIDUP BERSIH DAN SEHAT DENGAN KEJADIAN DIARE ANAK - Alamsyah Lukito (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2018)
Diarrhea the second leading cause of death in children under five years old. with morbidity and mortality rates are relatively high in many countries, especially in developing countries, and as one of the major causes of morbidity and mortality of children in the world. Especially in northern Sumatra in 2012, of the estimated 559 011 cases of diarrhea are found and dealt with is as much as 216 175, or 38.67%, resulting in morbidity IR (incedent Rate) diarrhea per 1,000 population reaches 16.36%. This study aims to determine the relationship of the level of knowledge of mothers on Behavior Clean and Healthy Lifestyle (PHBS) with the incidence of diarrhea in health centers johor field in 2017. This research is an analytic descriptive correlation with cross sectional approach. The samples using proportionate stratified random sampling technique with sample number 64 data collection using questionnaires. Data were analyzed using chi square with Continuity correction. The results showed that of the test statistics Chi squaer obtain the value of p <0.05 can be concluded that there is a significant relationship between knowledge tehadap behavior of clean and healthy mother with the incidence of diarrhea in children in Puskesmas Medan Johor. The level of knowledge of the Clean and Healthy Lifestyle (PHBS) affect the incidence of diarrhea was one mother's lack of knowledge to recognize the causes of diarrhea incidence and wrong behavior in a child care health centers in the scope of Johor field.